Inducible Clindamycin resistance among clinically isolated Methicillin resistant Staphylococcus aureus (MRSA) at tertiary care hospitals in Bangladesh - Shweta, Dipita Saha (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirement for the degree of Master of Science in Biotechnology, 2024.